Developing problem-solving skills in ratios and scales for grade 6 students using cooperative learning with TGT and graphic organizer techniques - Phomlao, Tanakron; Yonwilad, Wannatida (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This research aimed to develop problem-solving skills in ratios and scale by employing cooperative learning through the Team-Games-Tournaments (TGT) technique in conjunction with the graphic organizer. Students often struggle to understand the relationship between quantities, leading to difficulties in applying ratios and scale accurately. method for sixth-grade elementary school students. The study focused on a target group of 39 sixth-grade students from a medium-sized school in Somdej District, Kalasin Province, during the first semester of the 2024 academic year. The researchers selected participants using purposive random sampling. The research tools included eight lesson plans designed with the TGT technique and graphic organizer methods and a test to evaluate problem-solving skills in ratios and scale. The study adopted an Action Research approach, organized into two action cycles. The first cycle implemented lesson plans 1-4 and included a test featuring five open-ended problems on ratios. Action Cycle 2 utilized lesson plans 5–8 and included a test with five subjective issues on the scale. Statistical tools for data analysis included mean, percentage, and standard deviation. The results indicated that students' problem-solving skills in ratios and scale improved, with an average score of 62.62% in Action Cycle 1 and 74.26% in Action Cycle 2. The second cycle exceeded the 70% criterion with statistical significance at the .50 level.